2021
DOI: 10.1111/and.14259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paternal health on pregnancy loss—A review of current evidence

Abstract: Pregnancy loss has multifactorial causes, and the maternal risk factors are the most investigated. Therefore, this review investigates the current literature regarding the effect of paternal health on pregnancy loss. This review is conducted according to the PRISMA guidelines. The electronic databases PubMed and Medline were the primary sources of information. The online tool covid ence.org was used for the screening process. The Newcastle-Ottawa Scale was used for assessment of risk of bias across the non-RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Another limitations of the study was that we did not obtain any information regarding the paternal factors as well as information regarding cases reported with problems in the male counterpart with regards to smoking, obesity and diabetes mellitus in the absence of male factor abnormalities. This is because recent studies have shown that advanced paternal age is also associated with an increased risk of spontaneous recurrent miscarriage ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitations of the study was that we did not obtain any information regarding the paternal factors as well as information regarding cases reported with problems in the male counterpart with regards to smoking, obesity and diabetes mellitus in the absence of male factor abnormalities. This is because recent studies have shown that advanced paternal age is also associated with an increased risk of spontaneous recurrent miscarriage ( 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we added three risk factors of paternal indicators to the mutually adjusted model for a subset of 54,248 observations that had collected information on fathers. Growing literature indicates that paternal biological characteristics play a critical role in pregnancy outcomes, 22 yet the data collection process on the related indicators lags behind – among the 50 countries, only 13 of them collected paternal indicators. Therefore, we did not include them in the primary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As indicated above, we already know that DNA damage in human spermatozoa increases as an exponential function of paternal age ( Evenson et al , 2020 ). A significant proportion of these DNA-damaged cells must retain the capacity for fertilization because we see correlations between paternal age and both the quality of blastocysts created during ART ( Donatti et al , 2023 ) as well as the incidence of spontaneous early pregnancy loss ( Brandt et al , 2022 ). Once fertilization has occurred, the oocyte will have a brief period time to repair the DNA damage brought in by the fertilizing spermatozoon before S-phase of the first mitotic division is activated.…”
Section: Paternal Ageing and De Novo Mutationsmentioning
confidence: 99%